Particulate air pollution and daily mortality: Can results be generalized to Latin American countries? - ROMIEU ISABELLE; BORJA-ABURTO VÍCTOR HUGO (Instituto Nacional de Salud Pública, 1997)
Objective. Recently, a series of reports, based on ecological analyses of routinely collected data, have shown positive associations between measures of particle concentration and daily mortality counts in various cities of the US and Europe. Material and methods. We reviewed the process of generalization of these results to Latin American countries addressing possible differences in air pollution mixtures, exposure profiles, and population susceptibility. Results. A limitation to the process of generalization is the lack of a well-established biological mechanism by which particles may act on daily mortality. Also, sources and levels of ambient air pollution as well as population characteristics and habits vary widely between Northern communities of Europe and the US, and Latin American countries, which impairs the process of generalization. However, results of studies conducted in Latin American countries suggest a similar effect to that observed in Northern countries of Europe and the US. Conclusions. Despite uncertainty about the mechanism, there is sufficient evidence that particles are harmful for health. Control measures of particle emission are urgently needed in Latin American countries. Given the potential of misclassification of exposure, the dose-response relationship observed in Northern Europe and the US may not be adequate for Latin American populations. There is a need for a new generation of epidemiological studies including a specific assessment of exposure to fine particles and of events surrounding death.